Reputation repair and corporate donations: An investigation of responses to regulatory penalties - Xue Xia; Fei Teng; Xiaolong Gu (China Journal of Accounting Research, 2019)
According to the risk management and reputation insurance theory of corporate social responsibility, corporate donations can help a company to repair its reputation after a crisis. This study uses a propensity score matching-difference in difference (PSM+DID) methodology to investigate the charitable donation activities of companies that have been subject to regulatory penalties. The analysis of a sample of A-share listed companies in the 2004-2016 period shows that companies significantly increase their charitable donations after regulatory penalties, but this effect weakens over time. Further analysis reveals that non-state-owned companies, companies with higher ownership concentrations, and companies receiving severer penalties are more motivated to make donations after regulatory penalties. By studying the reputation repair behavior of companies that have been subject to regulatory penalties, this study offers further support for the risk management and reputation insurance theory of corporate social responsibility. It also enriches our understanding of companies' active responses to regulatory penalties and provides insights into companies' motives for making charitable donations.
Keywords: 650; Donation; Regulatory penalty; Reputation repair